Chaotic Characteristics of Vertical Cavity Surface Emitting Lasers Subject to Optoelectronic Feedback - Tahir, Fedil Rahma (Iraqi Journal for Electrical and Electronic Engineering, 2006)
In this study, the chaotic dynamics observed from a vertical cavity surface emitting lasers (VCSELS) subject to delayed optoelectronic feedback are investigated. The theoretical investigation is performed by using a MATLAB software package. The nonlinear dynamics of a VCSEL are examined using a single mode rate equations model. The key role played by system parameters such as delay time and the feedback strength on laser chaotic dynamics is addressed.